Manejo integrado del Picudo negro Rhynchophorus palmarum Linnaeus en el cultivo de palma aceitera Elaeis guineensis Jacq - Franco Olivo, Hanne Owen (2024)
This document deals with the integrated management of the Black Weevil Rhynchophorus palmarum Linnaeus in the oil palm crop Elaeis guineensis Jacq. The objectives were to detail the symptoms and damage caused by the black weevil in the oil palm crop and to establish the integrated management methods of the black weevil R. palmarum in the oil palm crop E. guineensis. The conclusions determined that the external symptoms of infested palms include a progressive yellowing of the leaf area, damage to emerging leaves and necrosis in the flowers. The presence of internal galleries, as well as the deterioration of leaves and stems caused by larvae, can be easily identified in plants with a high degree of infestation. Damaged plant tissues emit strong and characteristic odors. Despite frequent attempts, chemical control of the insect is not successful. The cultural practice of burning affected trees reduces infestation levels. The most commonly used control methods are based on the capture of adults using traps baited with decomposing plant materials, such as palm tissue. Several types of traps have been proposed to attract insects and subsequently eliminate them by applying chemicals such as trichlorfon and ethyl pirimiphos. It is observed that yellow traps show greater effectiveness compared to those of different colors. Newer versions of the trap incorporate natural or synthetic aggregation pheromones to enhance insect attraction.